The role of civics teachers in improving the character of tolerance in class X students of Al Hidayah High School - Zulkifli Amin; Syafaruddin Munthe (Indonesian Journal Education, 2026)
This research aims to examine the role of Civics teachers in strengthening the character of tolerance among students. Civics teachers have a significant responsibility in instilling the values of tolerance through classroom learning. This study employs a qualitative research method, with data collected through observation, interviews, and documentation. The findings indicate that teachers play a crucial role in strengthening the character of tolerance, which serves as a bridge for instilling tolerance values in students. The study identifies five steps in implementing tolerance education in the classroom. First, teachers analyze basic competencies by identifying the character values contained in the learning materials. Second, they prepare a lesson plan that focuses on tolerance-related content. Third, they implement the learning process according to the planned activities. Fourth, they conduct assessments to evaluate students’ understanding and development. Finally, they evaluate the learning outcomes to determine the extent to which students have understood and internalized the values of tolerance taught by the teacher.